2020
DOI: 10.5194/isprs-archives-xliv-3-w1-2020-87-2020
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Representation and Management of Infectious Disease Data on a City Scale, Case Study of St. Petersburg, Russia

Abstract: Abstract. In 2019–2020, we conducted a set of case studies devoted to the investigation and design of a methodology for GIS-based support of medical administration and planning on a city scale when accounting and controlling infectious disease. The studies were conducted for the administrative territory of St. Petersburg city (Russia), and were based upon the medical statistics data collected and accounted by St. Petersburg medical administration. The statistics included data on tuberculosis, human immunodefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…In Russia, a number of authors have successfully applied WebGIS to mapping the COVID-19 epidemic. Kuznetsov et al (2020b) focused on the investigation and design of the methodology and software prototype for GIS-based support of medical administration and planning on a city scale when accounting and controlling infectious diseases. Later, with the aim of evaluating the usefulness of Internet queries related to the smell to assess the effectiveness of anti-epidemic measures of preventing the spread of COVID-19 in some regions of Russia, Momynaliev et al (2021) concluded that the rise in the sudden interest in smell among Internet users can be seen as a valuable minimally invasive indicator of the spread of the coronavirus in the population, as well as to assess the effectiveness of anti-epidemic measures against COVID-19.…”
Section: Webgis-based Mappingmentioning
confidence: 99%
“…In Russia, a number of authors have successfully applied WebGIS to mapping the COVID-19 epidemic. Kuznetsov et al (2020b) focused on the investigation and design of the methodology and software prototype for GIS-based support of medical administration and planning on a city scale when accounting and controlling infectious diseases. Later, with the aim of evaluating the usefulness of Internet queries related to the smell to assess the effectiveness of anti-epidemic measures of preventing the spread of COVID-19 in some regions of Russia, Momynaliev et al (2021) concluded that the rise in the sudden interest in smell among Internet users can be seen as a valuable minimally invasive indicator of the spread of the coronavirus in the population, as well as to assess the effectiveness of anti-epidemic measures against COVID-19.…”
Section: Webgis-based Mappingmentioning
confidence: 99%
“…11). Модуль разработан с использованием стандартных (для QgIS) средств QgIS plugin Builder 6 . После ввода исходных геокодируемых данных в поля формы, в результате автоматического выполнения забросов к необходимым веб-сервисам, модуль сохраняет данные в файл в формате geoJSoN 7 , который может быть отображён в QgIS в виде слоя карты, содержащего геокодированные геометрию и атрибуты.…”
Section: результаты исследования и их обсуждениеunclassified
“…Улан-Баторская, д. 1, 64033, Иркутск, Россия; e-mail: postman@irigs.irk.ru6 Институт географии имени В.Б. Сочавы СО РАН, ул.…”
unclassified
“…The topic of GIS technology use in medicine has been studied by us since the 2019. We have developed our own geocoder upon Nominatim OpenStreetMap geocoding engine (Kuznetsov at al., 2020a), and have used Web GIS to detect the problems and successes in the fight against tuberculosis in St. Petersburg (Kuznetsov at al., 2020b). Initially, we worked on detection of the tuberculosis infection and other diseases hotbeds, based on residence data of patients.…”
Section: Introductionmentioning
confidence: 99%